Cultural studies and discourse analysis : a dialogue on language and identity - Barker, Chris, 1955- (SAGE, 2001)
This text shows that critical discourse analysis is able to provide the analytic context, skills and tools by which we can study how language constructs, constitutes and shapes the social world.